Study of Association between Social Adjustment and Spiritual Health in Qom University of Medical Sciences Students - zahra Aliakbarzade arani; Hamid Asayesh; Mahsa Hajimohamadhoseini (Health, Spirituality and Medical Ethics, 2017)
Background and Objectives: Admission to university is considered an opportunity to learn more and mentally grow further. At the same time, it is considered a stressor by some students and causes maladaptive reactions in them. This study was conducted to investigate the association between social adjustment and spiritual health in university students.